Da tela grande à palma da mão: as novas configurações dos audiovisuais no tripé produção, exibição e consumo - Quintas, Claudio (2022)
This research presents a deep study questioning the reconfigurations in the field of audiovisual production with the entry into the scene of VOD (Video on Demand) platforms. Emerging just over a decade ago, these platforms originally distributed audiovisual content, but in recent years they have started to produce their own original productions. The study focuses specifically on Netflix, selected here as the object of study, focusing on its performance in the Brazilian market. To deepen this analysis, we focused on two original Netflix productions filmed in Brazil: the series 3% and the feature-length film Modo Avião, defined as our empirical objects. Our choice is justified by the fact that both productions were made in the country, with Brazilian technicians and cast, and have achieved considerable international success in terms of global audience ratings. For its development, we worked with a methodological approach that articulated bibliographical research and empirical research, with the intention of investigating the possible local elements or strategies of such productions that, in the understanding of the platform’s executives and the filmmakers, may have contributed to its good performance in terms of penetration of the international audience.